Assesing Knowledge and Practices About Birth Preparedness Plans Amang Pregnant Women In Mukono District - Virginia Plan . (Kampala : Uganda Christian University Mukono, 2008)
Descriptive Cataloguing Uganda Christian University Mukono . MPHL Dissertation
Includes References (p. 36-37) appedixes (p. 38-55)